Post Marketing Surveillance on Different Brands of Propranolol Tablets - Darine Mousa Abozaid; Wedad Masoud Saleh; Azah Manbi Ali (African Journal of Advanced Pure and Applied Sciences, 2025)
Non-selective beta-adrenoceptor blockers like propranolol are commonly administered to manage cardiac issues and high blood pressure. This research attempts to ascertain whether specific brands of propranolol tablets available in Al Bayda, Libya, meet the specifications established by the US Pharmacopoeia or the British Pharmacopoeia and fulfill up to the claims stated on their labels. From a variety of retail pharmacies in Al Bayda, Libya, four different brands of propranolol tablets were randomly selected. Several quality control tests were conducted as part of the evaluation procedure. The findings demonstrated that every brand had uniformity in diameter, thickness, and weight as well as acceptable external qualities. Every brand has proven to have enough mechanical strength to withstand crumbling and breaking. Additionally, all samples (with the exception of one brand) satisfied requirements for drug content and disintegration time. All products under investigation met pharmacopoeial requirements, according to the dissolution profile, with the exception of brand Pr2. Consequently, all brands of propranolol tablets that were assessed, with the exception of brand Pr2, were determined to be of satisfactory quality. However, their dissolution profiles were not comparable to those of the innovator, and they could not be used interchangeably.